Computer-Assisted Instructional Strategies and Learning Outcomes of Pupils in Pre-Basic Private Schools in Southwestern Nigeria - Oluwatoyin, Fashiku, Christopher; Olujoke, Jembola Emily; Baba, Ayoku Oba (American Journal of Education and Learning, 2022)
The study was on the influence of computer-assisted learning instructional strategies on learning outcomes of pupils in Pre-Basic private schools in Southwestern Nigeria. The descriptive survey research design was used in the study. The population comprised 14,266 teachers in Southwestern Nigeria’s pre-basic and primary schools. A sample of 378 primary school teachers were selected using a multi-stage sampling procedure. The study used the Management of Computer Assisted Learning, Instructional Strategies and Learning Outcomes in Pre-basic Schools Questionnaire (MACALISLOPS-Q), Teachers’ Observation Schedule on CAL Application (TOSCALA) and Test of Skill Acquisition on CAL in Pre-basic Schools (TESACALPS) for data collection. Data collected were analysed using percentages and mean scores for research questions while the hypotheses were tested using Analysis of Variance. The results showed that the types of CAL facilities and equipment used in teaching in the study area were Computer desktop/laptop (81.2%), interactive whiteboard (53.9%), television (75.6%), smartphones 59.4%, Digital Video Disks and Compact Disks (69.4%). Results further showed a significant influence of CAL on children’s Literacy and Numeracy (F-= 4.517, p<0.05), The study concluded that Management of Computer Assisted Learning (CAL) and instructional strategies have a significant influence on learning outcomes of private pre-basic school children in Southwestern Nigeria it was recommended among others that: stakeholders in education and non-governmental organisations should procure CAL facilities and equipment in Pre-Basic schools, the provided CAL technology should be well managed and appropriate instructional strategies should be used in facilitating learning among the children in Pre-Basic Schools in the study area.